The Degree of Practice of The Heads of The academic Departments at Al-Aqsa University to Manage Excellence and its Relation to Level of Improvement in Professional Performance of The Teaching Staff - Naji R Sukker (University of Science and Technology, Yemen, 2018)
The study aimed to determine the degree of practice of the heads of the academic departments at Al-Aqsa University to manage excellence, define the level of performance of faculty members, and examine whether there was a relationship between them. To achieve this, the descriptive approach was used by analyzing the information obtained through the study tools. Major findings include: the degree of management of excellence was medium (3.32), while the degree of job performance was moderate (3.28). The study also showed that there were no statistically significant differences attributed to the majority of the study variables. The exception was in the field of human development, for the type of academic department, in favor of the departments of science and in the field of empowerment of gender in favor of males. The study also showed that there was a positive and strong relationship between the heads of the academic departments at Al-Aqsa University to manage excellence in all fields and the level of improvement in the performance of the faculty members. The study recommended the implementation of several practical measures to improve the level of both the management of excellence and performance Keywords: Excellence management, Job performance, University education.